Ambient temperature induced Diels–Alder crosslinked networks based on controlled methacrylate copolymers for enhanced thermoreversibility and self-healability. Issue 42 (17th May 2017) - Jung, Sungmin; Kim, So Young; Kim, Jin Chul; Noh, Seung Man; Oh, Jung Kwon
Abstract : An effective thermoreversible crosslinked network fabricated at ambient temperature from a new, controlled methacrylate copolymer having reactive maleimide pendants and a trifunctional furan (TFu) exhibiting effective self-healability. Abstract : The development of covalently-crosslinked dynamic (reversible) networks has been extensively explored due to their built-in ability to self-repair damages, which prevents catastrophic failure of high-performance materials. Here, we report effective thermoreversible crosslinked networks fabricated at room or mild temperature from reactive blends consisting of a controlled methacrylate copolymer having maleimide pendants (CoPMA) and a trifunctional furan (TFu). Well-defined CoPMA is synthesized by controlled radical polymerization, ensuring predetermined chain lengths with narrow molecular weight distribution, and following post-modification through deprotection of pendant furan-protected maleimide groups, ensuring conversion to the corresponding maleimide pendants. The well-defined CoPMA is reactive to different amounts of TFu as a model polyfuran to form dynamic networks at ambient temperature through a click type Diels–Alder (DA) reaction. Comprehensive analyses indicate that the mole ratio of furan/maleimide group is an important parameter that significantly influences network flexibility. The developed dynamic networks crosslinked with thermo-labile DA cycloadduct linkages enable the dissociation and recombination through retro DA (rDA)/DA reactions at elevated temperatures. Such thermoreversibility, combined with balanced flexibility, allows for the development of dynamic network exhibiting effective self-healability at as low as 110 °C with great mechanical property restoration as well as healing elasticity through reversible restoration of viscoelastic properties.